(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, the characteristics of Eastern romanticism and social reality in the development of modern art are highlighted, and the analysis of images in the works of our modern artists is expressed in the images of dreams and dreams, legends and narratives related to the history and fate of the people.